Structure and expression of the gene encoding the vasoactive intestinal peptide precursor. - Linder, S (1987)
The gene encoding the human vasoactive intestinal peptide (VIP) and the histidine-methionine amide (PHM-27) peptide hormone was isolated from lambda phage libraries. The human gene was found to be composed of seven exons spanning approximately 9 kilobase pairs. The first exon codes for an untranslated leader sequence, and the second exon codes for a putative signal peptide. DNA sequences coding for the VIP and PHM-27 hormones are located in two different exons. Southern blot analysis with genomic DNA suggested that a single copy of the VIP/PHM-27 gene is present in the human haploid genome. The expression of VIP/PHM-27 precursor mRNA in various tissues in the rat was analyzed by RNA gel blot hybridization. In the organs examined, expression was only detected in the brain and duodenum. RNA isolated from various regions of the rat brain--including the cortex, hypothalamus, and hippocampus--hybridized to both VIP- and PHM-27-specific probes. The same pattern of hybridization was found when VIP- and PHM-27-specific probes were used, suggesting that possible differences in the localization of VIP and PHM-27 peptides between different brain regions cannot be accounted for by differential RNA processing.